JAWATAN KHALIFAH: ANALISIS MENGENAI KEHUJAHAN SHAYKH MUHAMMAD MARCI DALAM KARYANYA LIMADHA AKHTARTU MADHHAB AL-SHICAH - Maafi Husin; ZAKARIA STAPA; JAWIAH DAKIR; Mohd Arif Nazri (Dirosat : Journal of Islamic Studies, 2016)
One of the most complicated problems faced by muslim community shortly after the death of prophet Muhammad PBUH was who to be elected as the khalifah after him. Abu Bakr was appointed finally as khalifah after Muhammad PBUH. But the Shi‘ites persist in arguing that Ali is the most eligible persons to be khalifah.Shaykh Muhammad Mar‘i is one among the Shi‘ites who defend the claim of Ali’s eligibility to be khalifah in his seminal work, Limādhā Ikhtartu Madhhab al-Shī‘ah. His arguments are based on the interpretation of āyat al-tablīghin Surah al-Mā’idah as well as the hadith of Ghadīr Khum. This article is an attempt to appraise critically those arguments according to the rules of Qur’anic exegesis and the principles of hadits evaluation proposed by scholars of Ahl al-Sunnah wa al-Jama‘ah. Based on these critical appraisal, the study reveals that his interpretation of āyat al-tablīgh  is simply inaccurate. There is clearly no indication in āyat al-tablīghof Ali’s eligibility to be khalifah after the death of Muhammad PBUH. Moreover, the study also proves that the hadits of Ghadīr Khum is too weak to be used as the basis for the above-mentioned claim of the Shi‘ite.